PRECIOUS-METAL MINERALIZATION OF MASSIVE PYRRHOTITE LENSES IN DZHUGDZHUR ANORTHOSITES - Solyanik A.N.; Oktyabrskiy R.A.; Lennikov A.M.; Pototskiy Yu.P.; Zarubin B.A.; Sapin V.I. (My University, 2001)
Data on platinum-group minerals (PGM): moncheites, sperrylites, Pt-Pd-telluride, and gold first discovered from massive pyrrhotite lenses in anorthosites of Lantar section of Dzhugdzhur massif are brought up in the paper. Low Bi and Ni content is specific feature of the examined moncheites unlike their analogues of sulfide Cu-Ni deposits of different formations. Sperrylite compositions do not reveal substantial chemical deviations in comparison with sperrylites from Cu-Ni deposits, except for Ni absence therein. Pt-Pd-telluride analysis was recalculated by the formula (Pd Te1+x) similar to the one described previously for palladium tellurides from magnetite pyroxenites of Gusevogorsk massif in the Urals Ridge. The following three types of native gold were distinguished: (1) one with elevated content of Ag (14.18-15.11 mass. %) and admixture of Pd (0.21-0.39 mass.%); (2) one more high-grade (6.99-7.39 mass. %) with platinum admixture less palladium; and (3) that from Krutoi Creek alluvium, not containing Ag, but with admixture of Cu (0.15 mass. %) and Pt (0.40 mass. %). The characterized precious-metal mineralization in sulfide lenses of Dzhugdzhur anorthosite complex, as well as that possibly caused by widely developed pyrrhotite impregnation of different intensity in Dzhugdzhur anorthosites, may have been the source of gold-bearing placers with PGM in Dzhugdzhur gold-bearing zone.